Oral Language Assessment in the Preschool and Primary Grades: Definitions, Measures, and Theoretical Lens - Heppner, Denise Hudspith (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
The overarching goal of this literature review is to improve the understanding of the importance of oral language to critical emergent literacy skills and provide an overview of available assessment measures for use within the classroom. An overview of the components of language (i.e., content, form, and use) is provided. Measures of oral language gleaned from a comprehensive literature review of the Education Resources Information Center (ERIC) database are discussed, organized according to the components of language they are assessing. An examination of the theoretical foundations of language acquisition and development provides an orienting framework for educators.